(untitled) (Neliniini Kolyvannya, 2003)
This paper deals with a new optimal existence theory for single and multiple positive periodic solutions to functional differential equations by employing a fixed point theorem in cones. We illustrate our theory by examining several biomathematical models. The paper improves and extends previous results in the literature.